Effects of extracellular calcium ion on the germination of Gelidium floridanum (Rhodophyta, Gelidiales) tetraspores - Bouvie, Fernanda; Pereira, Débora Tomazi; Ouriques, Luciane Cristina; Costa Puerari, Rodrigo; Matias, Willian Gerson; Hayashi, Leila; Simioni, Carmen (Elsevier, 2025)
Gelidium species cultivation is rare because establishing one methodology is difficult, or even when this is possible, the application to the field can be a challenge. These difficulties are associated with the low growth rates related to the availability of nutrients in culture media. The goal of this study was to observe the role of extracellular calcium on spore germination. We investigated the effects of EGTA (a calcium-chelating agent) and CaCl₂ (a source of extracellular calcium) in the germination of Gelidium floridanum tetraspores. Tetraspores were cultivated with EGTA and CaCl2 for 6 hours when the germ tube formation process was initiated. Adhesion, germination rate, and morphology analysis of the tetraspores were performed by light microscopy; analysis of actin filaments and cell wall (cellulose) by confocal scanning laser microscopy; and ultrastructure analysis by transmission electron microscopy (TEM). There was no germination of tetraspores, and adhesion was reduced when treated with EGTA. A higher germination rate and acceleration of this process was observed when treated with CaCl2, indicating that germination and adhesion are calcium-dependent. Tetraspores treated with EGTA show no cell wall formation or polarization of actin filaments, confirmed by TEM, indicating interference with intracellular calcium homeostasis and disorganization of organelles. These results contrasted with those observed in CaCl2 treatment, where a small amount of extracellular calcium accelerates the germinative process. Based on these results, we conclude that this species has the germination dependent on extracellular Ca2+ influx, and its suppression may cause the interruption of Ca2+ -dependent signaling required for tetraspores germination.
Keywords: Fisiología vegetal; Esporas (Botánica); Rodofíceas; Calcium chloride; Spores; Actin; EGTA; Electron microscopy; Red algae